Statins Use in Veterans With Peripheral Artery Disease: Insights From the PEARLS Study - Rohit Nathani; Cathy Nguyen; Qiang Li; Mary Vaughan-Sarrazin; Mohammad Al-Garadi; Nicole Minniefield-Young; Kim Smolderen; Shirling Tsai; Shipra Arya; Joshua A. Beckman; Brian C. Lund; Saket Girotra (Circulation: Population Health and Outcomes, 2026)
BACKGROUND: Guidelines recommend high-intensity statins in patients with peripheral artery disease (PAD). We examined contemporary use of statins among real-world patients with a new diagnosis of PAD. METHODS: Within a national registry of Veterans with incident PAD, we used pharmacy claims data to determine active statin use within 1 year of PAD diagnosis. We also used laboratory data to evaluate lipid levels. Hierarchical multivariable logistic regression was used to identify variables associated with the use of any statin and high-intensity statin 1 year after PAD diagnosis and quantify variation in statin use across sites. RESULTS: Among 91 970 patients with PAD alive at 1 year, the median age was 70 years, 97.2% were men, and 18.6% were Black. At 1 year, 64 231 (69.9%) patients were on a statin, and 34 017 (37.0%) were on a high-intensity statin. Among nonstatin users, 53.4% (14 834/27 739) had not been prescribed a statin at any time in the preceding 3 years. Overall, the median low-density lipoprotein cholesterol was 81.6 mg/dL and was lower in those on high-intensity statins versus low/moderate-intensity statins versus no statins (72.2 versus 78.0 versus 100 mg/dL). Age, prior history of coronary artery disease, cerebrovascular disease, hypertension, diabetes, and current or former smoking history, obesity, and revascularization during the initial 6 months were associated with higher statin and high-intensity statin use (among statin users). At the site level, there was modest variation in statin use, especially high-intensity statins, which ranged from 20% to 54% with an overall median odds ratio of 1.39 (95% CI, 1.32–1.46). CONCLUSIONS: Nearly 70% of patients with PAD were receiving a statin within 1 year of PAD diagnosis. However, use of high-intensity statins and nonstatin lipid-lowering therapy remained suboptimal. Moreover, there was modest variation in use of statins, especially high-intensity statins, across sites, highlighting opportunities for improving guideline-concordant care in patients with PAD.